Single sitting multimodality management of hemorrhoid - Singh, Mahendra P. (International Surgery Journal, 2021)
Background: It is usual to face clinical complexity in piles patients. They usually present with variable number of pile masses and in different grades of progression. This led to the idea of offering concomitant single stage management in our hemorrhoid patients matching to our criteria. We conducted hospital based descriptive study among the patients coming to my clinical practice falling in grade-1-3. Methods: All the patients falling in grade-1-3 and matching to our criteria were included. The study was conducted from January 2012 to December 2020. Place of study was basically at two centres: Karamdeep medical centre, Kanpur and Mayo health care, Mohali. Total number of patients were 581. Patients having grade-4 piles and with local co-morbidities were excluded from the study. Modalities of treatment used were sclerotherapy, band ligation and hemorrhoidectomy. Results: Patients managed were divided into four groups – group 1 included patients with piles in grade-1; group-2 included patients having piles in grade-1 and 2; group-3 included patients having piles in grade-1 and 3; and group-4 included patients having piles in grade-1, 2 and 3. Total 952 pile masses were treated in 581 patients. Sclerotherapy was required in 732 (77%) masses, banding in 99 (10.3%) masses and surgery in 122 (12.7%) masses. Conclusions: Concomitant treatment policy proved to be comprehensive way to tackle pile patients of grade-1-3. Mixed and matched method using surgical and non-surgical modalities in a single sitting proved to be beneficial. 86.4% cases were cured this way. Cost of the treatment was economical with lesser complications including local mutilation and better quality of life.